ANÁLISIS DE LA ESTRUCTURA DE ACCESO Y CONFIGURACIÓN DE LA OLT MARCA “DAYTAI” DE LA EMPRESA ISP MAXITEL DEL CANTON VINCES - MALDONADO GUERRERO, STALIN FERNANDO (2019)
Currently we live in the time of information technology and we can see the great growth and progress that this has, this has allowed more institutions or various companies to grant software and hardware. With the passage of time the company and many organizations are dependent on the largest extent of information on their technologies and their communications, this information is the most valuable resource of any organization, and especially for companies operating in a certain sector. in which this is their main and often their only resource. The companies base their success to the great generality of organizations in what has to do with the information technology since it is used a lot, when managing the activities that are done in each department of an organization in its different areas. Maxitel is a company that was born in 2008 due to the increasing demand of the citizens of Vinceña to have a fast and efficient communication service. The same that remains free of errors, and in the same way to maintain the confidentiality of the information required by customers. The company Maxitel ISP (Internet Service Provider) is located in the streets between Av. Jaime Roldós between Los Ríos and Coto Infante Vinces Province of Los Ríos, this company is dedicated to providing internet services to all people who are in the canton of Vinces and surrounding areas it should be noted that the Maxitel company is slowly opening up its market to other parts near its center, such as the cantons surrounding the canton of Vinces.